OP4 Perivascular fat attenuation index mapping around the right and left coronary artery independently predict cardiac mortality. (7th September 2020) - Kotanidis, Christos P; Oikonomou, Evangelos K; Marwan, Mohamed; Thomas, Katharine E; Alashi, Alaa; Antonopoulos, Alexios S; Shirodaria, Cheerag; Neubauer, Stefan; Channon, Keith M; Achenbach, Stephan; Desai, Milind Y; Antoniades, Charalambos
Abstract : Introduction: Coronary inflammation induces spatial changes in perivascular adipose tissue (PVAT) composition, which can now be detected as spatial changes in PVAT attenuation quantified by the perivascular Fat Attenuation Index (FAI) on coronary computed tomography angiography (CCTA). We assessed the ability of perivascular FAI mapping around the right and left coronary territories to independently stratify future cardiac risk. Methods: This was a post-hoc analysis of the CRISP-CT (Cardiovascular RISk Prediction using Computed Tomography) study that included 3912 patients with an average age of 55.7 years (standard deviation [SD]: 13.7 years). Perivascular FAI mapping was performed around the proximal right (RCA) and left anterior descending (LAD) coronary arteries. FAI was calculated based on the weighted average attenuation of PVAT using the CaRi-HEART algorithm, as previously described. The independent association with future incidence of cardiac death was assessed in adjusted Cox regression models. Results: Over a median follow-up period of 5.6 years, 74 cardiac deaths were recorded. The cross-sectional association between perivascular FAI around the RCA and LAD at baseline was found to be moderate (R2=0.36, P<0.001). Interestingly, both higher peri-RCA and peri-LAD FAI values were independently associated with a higher risk of cardiac mortality, following multivariable adjustment for age, sex, hypertension, hyperlipidemia, diabetes mellitus, smoking, epicardial adipose tissue volume and coronary artery disease (≥50% stenosis) (adjusted Hazard Ratio [95% confidence interval] of 1.70 [1.23–2.35], P=0.001 & 1.55 [1.12–2.14], P=0.008 per 1 SD increments, respectively) Conclusion: Perivascular FAI around the coronary arteries is characterised by anatomical/regional variability, and its values are affected by the coronary segment interrogated. Non-invasive characterization of coronary inflammation using CCTA-derived FAI should include a comprehensive assessment of both coronary arteries in order to better characterize the inflammatory residual risk of each patient.